Tf2NH-catalyzed 1,6-conjugate addition of vinyl azides with p-quinone methides: a mild and efficient method for the synthesis of β-bis-arylamides - Rathod, Jayant; Sharma, Brijesh M.; Mali, Pramod S.; Kumar, Pradeep (Synthesis, 2017)
Tf2NH-catalyzed tandem 1,6-conjugate addition/Schmidt type rearrangement using vinyl azides and p-quinone methides to access a variety of β-bis-arylated amides is reported. The method is quick, efficient, mild, and high yielding with broad substrate scope.

Transition metal catalysis-a unique road map in the stereoselective synthesis of 1,3-polyols - Kumar, Pradeep; Tripathi, Divya; Sharma, Brijesh M.; Dwivedi, Namrata (Organic & Biomolecular Chemistry, 2017)
The present review summarizes recent diverse reactions employed in the formation of 1,3-polyols providing an overview of the mechanistic pathway and the enantioselectivity obtained, in terms of the properties of transition metals directly involved in the catalytic transformations and their interaction with various ligands.